MicroRNA-146a: A Dominant, Negative Regulator of the Innate Immune Response - Saba, Reuben; Sorensen, Debra L.; Booth, Stephanie A. (Frontiers in Immunology, 2014)
MicroRNAs (miRNAs) are a class of small non-coding RNA molecules that can play critical roles as regulators of numerous pathways and biological processes including the immune response. Emerging as one of the most important miRNAs to orchestrate immune and inflammatory signaling, often through its recognized target genes, IRAK1 and TRAF6, is microRNA-146a (miR-146a). MiR-146a is one, of a small number of miRNAs, whose expression is strongly induced following challenge of cells with bacterial endotoxin, and prolonged expression has been linked to immune tolerance, implying that it acts as a fine tuning mechanism to prevent an overstimulation of the inflammatory response. In other cells, miR-146a has been shown to play a role in the control of the differentiation of megakaryocytic and monocytic lineages, adaptive immunity and cancer. In this review, we discuss the central role prescribed to miR-146a in innate immunity. We particularly focus on the role played by miR-146a in the regulation and signaling mediated by one of the main pattern recognition receptors, Toll/IL-1 receptors (TLRs). Additionally, we also discuss the role of miR-146a in several classes of autoimmune pathologies where this miRNA has been shown to be dysregulated, as well as its potential role in the pathobiology of neurodegenerative diseases.